Red dragon fruit (Hylocereus polyrhizus), a superfruit rich in betacyanins pigments with antioxidative potential for hepatoprotection: a review - Lim, Teck Wei; Lim, Renee Lay Hong; Pui, Liew Phing; Tan, Chin Ping; Ho, Chun Wai (Elsevier, 2025)
Red dragon fruit (RDF, Hylocereus polyrhizus) is an important source of betacyanins (0.79–1.17%) but seldom received attention, leading to a lack of review that mainly focuses on the RDF. This article is the first to provide a specific review on the complete taxonomy, common names, production, market and nutritional composition of RDF. In addition, the bioavailability [antioxidant (hepatoprotective) activity, bio-accessibility and absorption], stability and different conventional and new processing techniques (such as fermentation and food additive incorporation) of the RDF main bioactive pigments, betacyanins were also covered and discussed with other betacyanins sources. The journals, books, conference proceedings as well as electronic database were searched up to December 2024, using keywords, red dragon fruit, red pitaya/pitahaya, Hylocereus polyrhizus, betacyanins, betanin, antioxidant and liver. As compared to the red beetroot, the RDF pulp/flesh is relatively understudied and underexploited. Yet, RDF is a vital alternative source of betacyanins that can be developed into functional food products to take part in functional food security for the prevention of non-communicable diseases caused by oxidative stress to address the goals of the United Nations 2030 Agenda for Sustainable Development.